Inhibition of Adenosine Monophosphate–Activated Protein Kinase–3‐Hydroxy‐3‐Methylglutaryl Coenzyme A Reductase Signaling Leads to Hypercholesterolemia and Promotes Hepatic Steatosis and Insulin Resistance. Issue 1 (12th November 2018) - Loh, Kim; Tam, Shanna; Murray‐Segal, Lisa; Huynh, Kevin; Meikle, Peter J.; Scott, John W.; van Denderen, Bryce; Chen, Zhiping; Steel, Rohan; LeBlond, Nicholas D.; Burkovsky, Leah A.; O'Dwyer, Conor; et al.
Abstract : Adenosine monophosphate–activated protein kinase (AMPK) regulates multiple signaling pathways involved in glucose and lipid metabolism in response to changes in hormonal and nutrient status. Cell culture studies have shown that AMPK phosphorylation and inhibition of the rate‐limiting enzyme in the mevalonate pathway 3‐hydroxy‐3‐methylglutaryl (HMG) coenzyme A (CoA) reductase (HMGCR) at serine‐871 (Ser871; human HMGCR Ser872) suppresses cholesterol synthesis. In order to evaluate the role of AMPK‐HMGCR signaling in vivo, we generated mice with a Ser871‐alanine (Ala) knock‐in mutation (HMGCR KI). Cholesterol synthesis was significantly suppressed in wild‐type (WT) but not in HMGCR KI hepatocytes in response to AMPK activators. Liver cholesterol synthesis and cholesterol levels were significantly up‐regulated in HMGCR KI mice. When fed a high‐carbohydrate diet, HMGCR KI mice had enhanced triglyceride synthesis and liver steatosis, resulting in impaired glucose homeostasis. Conclusion: AMPK‐HMGCR signaling alone is sufficient to regulate both cholesterol and triglyceride synthesis under conditions of a high‐carbohydrate diet. Our findings highlight the tight coupling between the mevalonate and fatty acid synthesis pathways as well as revealing a role of AMPK in suppressing the deleterious effects of a high‐carbohydrate diet. Abstract : ‐ AMPK phosphorylation and inhibition of the rate‐limiting enzyme in the mevalonate pathway – HMG‐CoA‐Reductase (HMGCR) at Ser871 suppresses cholesterol synthesis in vivo in mice. ‐ When fed a high‐carbohydrate diet, HMGCR Ser871Ala mutant mice had enhanced triglyceride synthesis and liver steatosis resulting in impaired glucose homeostasis. ‐These findings reveal a critical role of AMPK in suppressing the deleterious effects of a high‐carbohydrate diet.